Axial strength of back-to-back cold-formed steel channels with edge-stiffened holes, un-stiffened holes and plain webs. (November 2020) - Chen, Boshan; Roy, Krishanu; Uzzaman, Asraf; Raftery, Gary; Lim, James B.P.
Abstract: Cold-formed steel (CFS) back-to-back channels are becoming a popular choice for use in load-carrying members in building structures. These built-up channels often include web holes for installation of services. Traditional web holes are un-stiffened, which can restrict the size and spacing of holes. Recently, a new generation of CFS channels with edge-stiffened holes has been developed and used widely in New Zealand. No research has been reported in the literature to investigate the axial strength of back-to-back channels with edge-stiffened holes. Experiments are required on back-to-back channels with edge-stiffened holes so to understand the effects of composite actions between the back-to-back channels on the axial strength of such channels. This paper presents a total of 162 new results comprising 27 axial compression tests and 135 finite element analysis (FEA) results on the axial strength of back-to-back channels with edge-stiffened holes, un-stiffened holes and plain webs. Prior to compression tests, initial geometric imperfections were measured using a laser scanner. Tensile coupon tests were also conducted to determine the material properties of both the flat and corner portions of the channels. The test results show that for the case of back-to-back channels with edge-stiffened holes, the axial strength increased by 6.6% on average, compared to a back-to-back plain channel. For comparison, the same section with un-stiffened holes had a 12.4% reduction on average in axial strength, compared to a back-to-back plain channel. A nonlinear elasto-plastic finite element (FE) model was then developed, and the results showed good agreement with the test results. The validated FE model was used to conduct a parametric study involving 135 FE models to investigate the effects of column slenderness, diameter of hole, screw spacing, stiffener lengths and stiffener fillet radius on the axial strength of such channels. Finally, the tests and parametric study results were compared against the design strengths calculated in accordance with the American Iron and Steel Institute (AISI) (2016) and Australian and New Zealand Standards (AS/NZS) (2018) for back-to-back plain channels and against the design equations of Moen and Schafer (2011) for back-to-back channels with un-stiffened holes. It was found that the AISI (2016) and AS/NZS (2018) are only 3% conservative to the test results. The Moen and Schafer equations (2008, 2009, 2011) are conservative by 21% on average for back-to-back channels with un-stiffened holes. Graphical abstract: Deformed shapes at failure from experiments and FEA. Unlabelled Image Highlights: A new generation of back-to-back CFS channels with edge-stiffened holes is examined. Results from an experimental regime and elasto-plastic finite element are reported. A parametric study involving 135 FE models was conducted. Variables included column slenderness, hole size, screw spacing, stiffener lengths and stiffener fillet radius. Edge stiffened hole-channels can outperform plain channels in terms of axial strength.